EVOLUTION OF INTERNATIONAL TRADE IN THE LIGHT OF THE WAR IN UKRAINE - Jitaru, Dorina (Modern engineering and innovative technologies, 2023)
The article focuses on the analysis of the main changes in trade policies and international trade flows in the light of the war in Ukraine, and the impact of other factors such as rising interest rates, inflationary pressures in many countries on internat